Using late-time optical and near-infrared spectra to constrain Type Ia supernova explosion properties. Issue 3 (30th March 2018) - Maguire, K; Sim, S A; Shingles, L; Spyromilio, J; Jerkstrand, A; Sullivan, M; Chen, T-W; Cartier, R; Dimitriadis, G; Frohmaier, C; Galbany, L; Gutiérrez, C P; et al.
Abstract: The late-time spectra of Type Ia supernovae (SNe Ia) are powerful probes of the underlying physics of their explosions. We investigate the late-time optical and near-infrared spectra of seven SNe Ia obtained at the VLT with XShooter at >200 d after explosion. At these epochs, the inner Fe-rich ejecta can be studied. We use a line-fitting analysis to determine the relative line fluxes, velocity shifts, and line widths of prominent features contributing to the spectra ([Fe ii ], [Ni ii ], and [Co iii ]). By focusing on [Fe ii ] and [Ni ii ] emission lines in the ∼7000–7500 Å region of the spectrum, we find that the ratio of stable [Ni ii ] to mainly radioactively produced [Fe ii ] for most SNe Ia in the sample is consistent with Chandrasekhar-mass delayed-detonation explosion models, as well as sub-Chandrasekhar mass explosions that have metallicity values above solar. The mean measured Ni/Fe abundance of our sample is consistent with the solar value. The more highly ionized [Co iii ] emission lines are found to be more centrally located in the ejecta and have broader lines than the [Fe ii ] and [Ni ii ] features. Our analysis also strengthens previous results that SNe Ia with higher Si ii velocities at maximum light preferentially display blueshifted [Fe ii ] 7155 Å lines at late times. Our combined results lead us to speculate that the majority of normal SN Ia explosions produce ejecta distributions that deviate significantly from spherical symmetry.